Penerapan Strategi Pembelajaran Kooperatif Dalam Pembelajaran PAI Untuk Meningkatkan Keterampilan Kerjasama Siswa - Halimatul Fijriah; Septia Yulia Ningsih; Gusmaneli Gusmaneli (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
The application of cooperative learning strategies is increasingly popular in improving students' cooperation skills at various levels of education. This research aims to determine the application of cooperative learning strategies in PAI learning to increase student cooperation. The data collection used by researchers is a literature study by studying and citing several sources from textbooks, articles, journals, modules and other publications. The research results show that the application of cooperative learning strategies can improve students' cooperation skills significantly. These findings provide an important contribution to the development of learning models that are oriented towards collaboration and cooperation in the educational environment.